Spatial variability of south Asian summer monsoon extreme rainfall events and their association with global climate indices. (15th September 2021) - Jamshadali, V.H.; Reji, M.J.K.; Varikoden, Hamza; Vishnu, R.
Abstract: The study explores the spatial variability and related characteristics of south Asian summer monsoon rainfall and extreme rainfall events based on APHRODITE rainfall products. An attempt was also made to investigate their association with global climate indices. Most of the South Asian regions are vulnerable to extreme rainfall events and many of these lead to major hydrological disasters. Such events are adversely affecting flora and fauna, causing large-scale damage to the livelihood and economy. We have analysed the characteristics of extreme rainfall events during the summer monsoon season for 65 years (1951–2015). The statistical method based on the percentile of daily rainfall amount (>99th percentile) was used to identify the extreme rainfall zones. We have also attempted to explore the spatio-temporal features and heterogeneity of these extreme events at a finer spatial resolution. We examined the linear trend of these extreme rain events on the spatial domain and found that extreme rainfall decreases over northcentral Indian and southwestern coastal belts. An increase in the frequency and amount of rainfall from extreme rain events were observed in the western coastal belts between 16° to 20° N and central Indian regions along with the coastal areas of Bangladesh and Myanmar. The linear trends of extremes exhibit remarkable differences from the trends of seasonal rainfall. The results from the probability density function (PDF ) analysis are also supporting the trend analysis of mean and extremes in all the five regions. It was also observed a distinct shift in the PDF curve during the pre and post 1980 periods. Moreover, we have analysed the relationship of various climate indices (Niño3.4, Modoki, DMI, PDO, AMO, and AZM) with the mean and extreme rainfalls in addition to the spatial trends. Most of the indices show a significant inverse relationship with mean and extreme rainfalls. The areas of significant correlation are less in the case of extreme rainfall while comparing with that of the mean rainfall. Highlights: Spatial variability of mean and extreme rainfall events were studied. It is found that most of the South Asian regions are vulnerable to extreme events. Extreme events shows a decrease in northcentral Indian and southwestern regions. Increase in frequency, intensity of extremes were found in central regions. The climate indices show significant inverse relationship with mean and extremes.